A Cognitive Analysis of Truck Drivers’ Right-hand Turns - Sieker, Tobias G.; Skulason, Thorgeir G.; Sletting, Kristian; Trolle, Trine K.; Hammershøi, Dorte (Proceedings from the Annual Transport Conference at Aalborg University, 2015)
This paper presents an investigation of truck drivers’ performance during right-hand turns performed in intersections with traffic lights in order to elicit the truck drivers’ domain, decision-making processes, and the strategies used while executing the turns. To gain knowledge about this, a truck driving instructor was interviewed, and four truck drivers were observed and interviewed. This resulted in a cognitive work analysis with the phases work domain analysis, control task analysis and strategies analysis. Through this study it is indi- cated that many different types of information are sought using several brief glances in mirrors, and the results shows how the front and near-zone mirrors were never used by the participants during the observed right-hand turns. Controlling the vehicle was found to be mainly automatic, whereas their focus is on the orientation about surroundings. Lastly, the drivers’ behavior is discussed in relation to change blindness, confirmation bias and schemes.